Effect of arsenate on germination and early development parameters of three forage leguminous plants (Revista de Ciências Agroveterinárias, 2020)
The Chacopampean plain is one of the most arsenic affected areas in Argentina, especially in groundwater, used both for animal drinking and forage irrigation. The main objective of this study was to determine the effect of arsenic (As) present in irrigation water on the germination parameters of red clover (Trifolium pratense L.), white clover (Trifolium repens L.), and alfalfa (Medicago sativa L.) seeds exposed to different concentrations of As(V). The germination and viability parameters of seeds from the three species were not affected by elevated concentrations of As. However, As significantly reduced the radicle and hypocotyl lengths of the three forage specimens. The inhibition level of the plants increased with the increase in the  concentration of As. Regarding to hypocotyl length/radicle length ratio, the results evidenced that both the hypocotyl and radicle of clover species are affected in the same degree, while alfalfa radicles seemed more affected than hypocotyls at higher concentrations of As. Our results showed that irrigation with solutions containing As affect seedling growth parameters differently in the three species, and the effect of As is mostly evidenced when in high concentrations.
Keywords: arsenic; forage; seeds